University Staff’s Perceptions of Community College Transfer Students’ Transition Experiences Within a “2+2” Pathway in an Asian Educational Context - Ching, Shirley Siu Yin; Kwok, Wilson Yeung Yuk; Ng, Jeremy Tzi Dong; Zhang, Lillian Weiwei; Ho, Ceci Sze Wing; Cheung, Kin (Frontiers in Psychology, 2022)
Various countries have alternative pathway policies for community college graduates to articulate to university study. However, limited studies have explored the university staff’s perceptions of community college “2+2” transfer pathway and their understanding about transfer students’ transition experience. This descriptive qualitative study was to fill this research gap. Forty-two academic and supporting staff participated in 34 interviews. They showed their confidence in the “2+2” pathway and commended TSs’ study attitudes and academic performances. They were sympathetic with the difficulties and challenges TSs faced, but felt incapacitated owing to government funding and policies restrictions. It is recommended that policies should be established on government and university levels to recognize and tackle TSs’ unique needs to alleviate their heavy workload through better articulation between community college and university studies. Improving articulation will allow TSs to have time for the social involvement in the university life and thus enhance their mental well-being.